Combined effects of chlorpyrifos and cyfluthrin on neurobehavior and neurotransmitter levels in larval zebrafish. Issue 10 (19th July 2022) - Zhang, Wanjun; Fan, Ruiqi; Luo, Sunlin; Liu, Ying; Jin, Yongpeng; Li, Yongchen; Li, Bo; Chen, Yiqiang; Jia, Li; Yuan, Xiaoyan
Abstract: Chlorpyrifos and cyfluthrin are insecticides commonly used in agriculture. The mixed residues of chlorpyrifos and cyfluthrin in the aquatic environment may have combined effects on nontarget species. Therefore, studying the combined toxic effects and mechanisms of pesticide mixtures is of great significance to environmental risk assessment. To evaluate the risk of combined exposure, we examined the effects of both compounds, separately and together, on motor activity, acetylcholinesterase (AChE) activity, and neurotransmitter levels in larval zebrafish. Chlorpyrifos exposure significantly reduced functional motor capacity (swim distance and velocity) and enhanced meandering, while cyfluthrin exposure alone had no significant effects on swim parameters. However, combined exposure significantly reduced total swimming distance and mean velocity and increased meandering. Both compounds alone and the combination significantly reduced AChE activity, and the combined effect was antagonistic. Combined exposure also significantly altered the concentrations of serotonin, serotonin precursors, and dopamine precursors, as well as concentrations of the amino acid neurotransmitters glycine, alanine, and aspartic acid. Combined exposure to chlorpyrifos and cyfluthrin exhibited distinct joint action modes in terms of neurobehavior, AChE activity, and neurotransmitter levels, thereby providing an experimental basis for assessing the combined exposure to chlorpyrifos and cyfluthrin's environmental risk. Abstract : Combined exposure to chlorpyrifos and cyfluthrin impaired larval zebrafish motor activity. Such phenomenon may be attributed to changes in AChE activity and neurotransmitter levels. Chlorpyrifos and cyfluthrin exhibited distinct joint action modes in terms of neurobehavior, AChE activity, and neurotransmitter levels in larval zebrafish.